Relationship of Leukocyte and Platelet Counts with NS-1 Antigen Examination Results in Suspected Dengue Fever Patients - Sherly Suryandari Utami; Djoko Priyatno (Poltekkes Kemenkes Mataram, 2026)
Dengue fever is still a global health problem, with high mortality rates due to dengue fever. Leukopenia and thrombocytopenia often occurs in dengue fever patients. Early detection of dengue virus infection through dengue NS-1 is needed to avoid delays in diagnosis where NS-1 has high sensitivity in detecting dengue virus infection in the early phase. A decrease in the number of leukocytes and platelets is a finding that can provide an indication of the severity of the disease and assist in the diagnosis of DHF. The aim of this research was to establish the relationship between total platelet and leukocyte counts and NS-1 antigen assay findings in individuals with suspected hemolytic disease of the liver (HDL). The research was quantitative, with an observational design and a cross-sectional approach. The study population consisted of 91 patients with suspected HDL at the Mayong II Jepara Health Center between January and December 2024. Total sampling was used. The findings indicated that males were the predominant group of patients with suspected HDL, and that 62% of them were in the 0-5 year age group. The average number of leukocytes in patients was 12,457 Â± 3,471 cells/mm3 of blood with the lowest leukocyte count of 3,400 cells/mm3 and the highest 20,500 cells/mm3. The average number of platelets was 162,626 Â± 72,930 cells/mm3 of blood with the lowest platelet count of 54,000 cells/mm3 and the highest 385,000 cells/mm3. The results of the NS-1 examination of suspected DHF patients were 69% positive and 31% negative. There was no relationship between the number of leukocytes and the NS-1 antigen examination (p value 0.220>0.05) but there was a relationship between the number of platelets and the NS-1 antigen examination (p value 0.00<0.05) in suspected DHF patients at Mayong II Jepara Health Center.